Determination of Total Flavonoid Content of Ethanol Extract and Ethyl Acetate Fraction of Avocado Seed (Persea americana Mill) by Visible Spectrofotometry Methods - Natasya, Siti Adinda; Nasution, M. Pandapotan; Nasution, Haris Munandar; Yuniarti, Rafita (Pustaka Media Publishing, 2025)
Avocado (Persea americana Mill.) has long been used in traditional medicine, and its seeds are known to contain flavonoid compounds, which are natural phenolics with antioxidant properties and potential therapeutic benefits. This study aims to identify the chemical compounds present in the ethanol extract and ethyl acetate fraction of avocado seeds, and to determine their total flavonoid content using UV-Visible spectrophotometry. This experimental study included sample collection, simplicia characterization, extraction, fractionation, phytochemical screening, and flavonoid quantification. Phytochemical screening showed that the ethanol extract contains alkaloids, flavonoids, tannins, saponins, triterpenoids, and glycosides, while the ethyl acetate fraction contains alkaloids, flavonoids, tannins, steroids, and glycosides. Flavonoid content was determined using quercetin as a standard. The results showed that the total flavonoid content in the ethanol extract was 8.655 ± 0.144 mgQE/g, while the ethyl acetate fraction contained 32.828 ± 0.105 mgQE/g. It can be concluded that the ethyl acetate fraction contains a significantly higher level of flavonoids compared to the ethanol extract.